2017
DOI: 10.23851/mjs.v28i1.310
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study between C-Reactive Protein and Procalcitonin in Iraqi Burn Patients

Abstract: Association between Procalcitonin (PCT) and C-reactive protein (CRP) and burn injury was evaluated in 80 burned patients from Al-Kindy and Imam Ali hospitals in Baghdad-Iraq. Patients were divided into two groups, survivor group 56 (70%) and non-survivor group 24 (30%). PCT was estimated using (Human Procalcitonin ELISA kit) provided by RayBio/USA while CRP was performed using a latex agglutination kit from Chromatest (Spain). Our results declared that the mean of Total Body Surface Area (TBSA %) affected were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
(7 reference statements)
1
2
0
Order By: Relevance
“…The sample size of 40 participants per group was determined based on a power analysis, which indicated that this number was sufficient to detect significant effects given the specific parameters and expected effect size of our research. Although this sample size is slightly smaller than the 45 to 50 participants utilized in related studies [ 45 , 46 ], it aligns with the general scale of previous research in this area. This clarification ensures a more accurate representation of our methodological approach and its alignment with established research standards in the field.…”
Section: Methodssupporting
confidence: 67%
“…The sample size of 40 participants per group was determined based on a power analysis, which indicated that this number was sufficient to detect significant effects given the specific parameters and expected effect size of our research. Although this sample size is slightly smaller than the 45 to 50 participants utilized in related studies [ 45 , 46 ], it aligns with the general scale of previous research in this area. This clarification ensures a more accurate representation of our methodological approach and its alignment with established research standards in the field.…”
Section: Methodssupporting
confidence: 67%
“…Among the 24 included studies [ 43 66 ], 16 had retrospective designs [ 43 46 , 48 50 , 53 , 56 , 59 , 60 , 62 – 66 ]. Studies were conducted in Turkey( n = 5) [ 45 , 49 , 50 , 62 , 64 ], South Korea( n = 2) [ 58 , 60 ], Portugal( n = 1) [ 53 ], Iraq( n = 2) [ 52 , 57 ] Uruguay( n = 1) [ 43 ], India( n = 2) [ 44 , 63 ], Indonesia( n = 1) [ 47 ], China( n = 5) [ 46 , 56 , 59 , 65 , 66 ], USA ( n = 1) [ 55 ], France( n = 1) [ 54 ], Italy ( n = 1) [ 61 ], Germany ( n = 1) [ 51 ], and Sweden( n = 1) [ 48 ]. Ten studies reported in-hospital mortality [ 43 – 45 , 47 , 51 , 54 , 59 , 62 – 64 ], three reported 90- day mortality [ 46 , 56 , 60 ], one reported 51-day mortality [ 65 ] and one reported 28-day mortality [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies assessed PCT level of patients at time of admission to the hospital [ 53 , 57 , 63 , 65 , 66 ], one study assessed it after informed consent [ 54 ], one reported it on Day 3 [ 51 ], one in the first 48 h after admission [ 62 ], one within 48 h after injury [ 59 ], one in less than 6 h after admission [ 52 ], and one study did not report this data [ 58 ] (Tables 1 and 2 ).…”
Section: Resultsmentioning
confidence: 99%